2019
DOI: 10.3390/w11040667
|View full text |Cite
|
Sign up to set email alerts
|

Water–Energy–Food Nexus Simulation: An Optimization Approach for Resource Security

Abstract: The water–energy–food nexus (WEF nexus) concept is a novel approach to manage limited resources. Since 2011, a number of studies were conducted to develop computer simulation models quantifying the interlinkage among water, energy, and food sectors. Advancing a nationwide WEF nexus simulation model (WEFSiM) previously developed by the authors, this study proposes an optimization module (WEFSiM-opt) to assist stakeholders in making informed decisions concerning sustainable resource management. Both single- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…These not only studied the internal relationship of the water-energy-food nexus, but also extended to the external relationship between society, economy, and ecology. In terms of qualitative research, many well-known nexus frameworks have also been proposed in the analysis of the connotation and operating mechanism of the water-energyfood nexus [12][13][14]. In terms of quantitative research, pressure-state-response (PSR) technology, the matter-element model, step-by-step methodology, and the non-linear optimization model are applied in the sustainability research of the water-energy-food nexus [15][16][17][18]: The structure path analysis method and the data envelopment analysis method have been carried out to study the input-output efficiency of water, energy, and food [19][20][21]; Technologies such as remote sensing and integrated resource management are used in the research of safety and risk control of the water-energy-food nexus system [22]; The system dynamics model has been proposed for simulating the interaction between water, energy, and food [23,24]; The principle of synergy has also been widely used in the study of the water-energy-food nexus [25][26][27]; In order to deal with the uncertainties in waterenergy-food management, some studies have proposed multi-stage fuzzy stochastic models [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…These not only studied the internal relationship of the water-energy-food nexus, but also extended to the external relationship between society, economy, and ecology. In terms of qualitative research, many well-known nexus frameworks have also been proposed in the analysis of the connotation and operating mechanism of the water-energyfood nexus [12][13][14]. In terms of quantitative research, pressure-state-response (PSR) technology, the matter-element model, step-by-step methodology, and the non-linear optimization model are applied in the sustainability research of the water-energy-food nexus [15][16][17][18]: The structure path analysis method and the data envelopment analysis method have been carried out to study the input-output efficiency of water, energy, and food [19][20][21]; Technologies such as remote sensing and integrated resource management are used in the research of safety and risk control of the water-energy-food nexus system [22]; The system dynamics model has been proposed for simulating the interaction between water, energy, and food [23,24]; The principle of synergy has also been widely used in the study of the water-energy-food nexus [25][26][27]; In order to deal with the uncertainties in waterenergy-food management, some studies have proposed multi-stage fuzzy stochastic models [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the water-energy-food nexus approach has been utilized via different dimensions in several studies under various objective functions in the form of optimization models (Jalilov et al, 2016;Dhaubanjar et al, 2017;El-Gafy et al, 2017;Stamou and Rutschmann, 2018;Zhang et al, 2018;Gonz´alez-Bravo et al, 2018;Si et al, 2019;Hu et al, 2019;Li et al, 2019;Liu et al, 2019;Zhou et al, 2019;Namany et al, 2019;Nie et al, 2019;Niu et al, 2019;Wicaksono et al, 2019;Sun et al, 2020;Ji et al, 2020;Falconer et al, 2020;Esmaeli and Roshandel, 2020;Yu et al, 2020;Medina-Santana et al, 2020;Sadeghi et al, 2020;Radmehr et al, 2021). For instance, Jalilov et al (2016) attempted to optimally allocate water resources in the Amu Darya River Basin using the concept of the water-energy-food approach through maximizing the net present value of the total benefits of agriculture and Hydroelectricity generated in the Rogun Dam.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of reviewing studies revealed that several methods have been employed to implement the water-energy-food nexus approach for optimal agricultural management. Most studies on the water-energy-food nexus in agriculture considered a combination of water and energy consumption benefit functions and environmental benefit functions as objective functions to design an optimal pattern regarding constraints of water and energy resources (Jalilov et al, 2016;Stamou and Rutschmann, 2018;Zhang et al, 2018;Li et al, 2019;Wicaksono et al, 2019;Ji et al, 2020;Radmehr et al, 2021). Nevertheless, some limited studies have been conducted in the agricultural sector and the basin level using a comprehensive index including water-energy-food nexus criteria (El-Gafy et al, 2017;Sadeghi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above definition, research in FEW nexus is therefore derived from the research that combines FEW securities. Indeed, most FEW nexus research takes resource security as their main goal [13,14].…”
Section: Introductionmentioning
confidence: 99%